Jewish stereotyping and anti-semitism in the plays of the Jew of Malta, The Merchant of Venice, and The Three Ladies of London - Alqudah, Mamoon Khaled
The blame game between Christians and Jews has been ongoing for centuries, and has affected society, culture, economy and even literature. In the Elizabethan age, there was no apparent presence of real Jews (except a few who converted to Christianity) as Jews were banned in England for three centuries. English playwrights Christopher Marlow and William Shakespeare revived the grotesque images of the Jews by reating contemptible as well as horrifying Jewish characters on the English stage. However, many studies claim that the Jews are unjustly judged and that the negative dominant portrayal of Jew is mainly due to the historical ideology in England. Many studies portray them as victims rather than victimizers. Hence, this study aims to analyse the Jews' social, political and religious status in the Elizabethan England through three chosen-plays - Marlowe's The Jew of Malta, Shakespeare's The Merchant of Venice, and Winston's The Three ladies of London - to understand the stereotypes and antiSemitism associated with Jews which continue till the present day. The research used the Critical Race Theory (CRT) as a framework to interpret the themes emerged from the thematic analysis. In conducting the thematic analysis, after familiarization with texts, initial codes were generated leading to the search for themes which were later reviewed, named and defined before the report is produced. The thematic analysis led to the emergence of several themes. The causes for the endless strife between Jews and Christians are religious differences, crimes linked to Jews hate crimes and economic rivalry. Anti-Semitic themes identified in the texts described Jews as blasphemous, cruel, murderers, unscrupulous usuries, miserly and cowards. Jewish characters such as Shylock and Barabas are labelled negatively as foul-mouthed individuals, unfriendly, deceitful, shrewd, scheming, racists, and manipulative. However, Gerontus is portrayed as honest, kind, forgiving, and virtuous. To conclude, Jews in the Jew of Malta and Merchant of Venice are depicted negatively in all the aspects examined (i.e social, political and religious aspects). These negative portrayals are strategically done to develop the stereotyping of the Jews and anti-Semitism in the Shakespeare and Marlowe's works hence contributing to the gloom-ridden narrative of Jews in the Elizabethan era. While Wilson's depiction of the Jewish characters in The Three Ladies of London is also negative; but not acute and scathing as in Marlowe and Shakespeare, rather it is subtle and alleviated as he does not present anti -Sernitism in a straightforward and direct way. This study concludes that Marlowe's play is rigidly anti-Semitic, Shakespeare's is less while Wilson's is the least.